Post-Divorce Polygamy in Tana Toraja: The Intersection of Islamic Law and Local Culture - Saidah, Saidah; Rukiah, Rukiah; Sunuwati, Sunuwati; Nasohah, Zaini (IAIN Manado, 2024)
The enforcement of women's rights concerning the restriction of polygamy during the iddah period following divorce is a significant problem in Islamic family law, especially within minority Muslim groups such as Tana Toraja. This paper examines a particular research gap: the inadequate comprehension of how local cultural practices affect the application of Islamic family law in minority settings. This study utilizes a legal methodology, integrating interviews with stakeholders from the local Religious Affairs Office and conducting document analysis of legal rulings, policies, and pertinent literature. The findings identify certain impediments, such as the impact of local cultural norms that frequently contradict Islamic legal principles and a lack of legal understanding within the community. The study proposes two principal recommendations to tackle these challenges: (1) improving legal education customized for the cultural context of minority Muslim communities, and (2) fortifying oversight mechanisms and law enforcement procedures via collaboration among local authorities, religious leaders, and community organizations.